A porous calcium silicate-supported antioxidant and its preparation method and application

By using the use of porous calcium silicate load -type anti -agent, the aging agent is evenly loaded on the surface of the polychitropic silicate, which solves the problem of migration between rubber anti -agent between the crosslinking network. Production cost.

CN116041793BActive Publication Date: 2025-01-24INNER MONGOLIA UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310182698.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-28
Publication Date
2025-01-24
Estimated Expiration
2043-02-28

AI Technical Summary

Technical Problem

The problem of existing rubber anti-aging agents migrating between elastomer macromolecular cross-linking networks has led to weakening of anti-aging effect and wasting of anti-aging agents. Commonly used carriers such as carbon black and graphene have environmental pollution, high production costs and serious agglomeration. question.

Method used

The use of calcium silicate as a carrier is used as a carrier. Through the mixing and deposition process with the agent, the antiplication agent is evenly loaded on the surface of the polynolite silicate, forming a polyunolic silicate load -type anti -agent.

Benefits of technology

The anti-aging agent is evenly distributed in the rubber, inhibits the migration of the anti-aging agent between the rubber cross-linked networks, improves the thermal oxidative aging resistance of rubber products, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116041793B_ABST
    Figure CN116041793B_ABST
Patent Text Reader

Abstract

The present invention provides a porous calcium silicate-loaded antioxidant and a preparation method and application thereof, belonging to the field of rubber processing aids. The porous calcium silicate-loaded antioxidant provided by the present invention comprises a porous calcium silicate carrier and an antioxidant loaded on the surface of the porous calcium silicate carrier; the mass of the antioxidant is 5 to 25% of the mass of the porous calcium silicate-loaded antioxidant. The present invention selects porous calcium silicate as a carrier of the antioxidant, which has a porous structure and a large specific surface area, and can play a good dispersing role on the antioxidant; and the porous calcium silicate carrier has a good adsorption effect, which is not only conducive to the antioxidant being firmly bonded to its surface and not easy to fall off, but also does not produce phase separation when added to rubber, and can effectively inhibit the migration of the antioxidant between the rubber cross-linked networks; in addition, the porous calcium silicate carrier has good dispersibility and a wide range of sources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rubber processing aids, and in particular to a porous calcium silicate-loaded antioxidant and a preparation method and application thereof. Background Art

[0002] Rubber antioxidant is a chemical added in the rubber production process that can delay rubber aging and extend the service life of rubber. Compared with rubber, antioxidant is a small molecule. Small molecule antioxidant can move between the cross-linked network of elastomer macromolecules and accumulate on the surface of elastomer products to produce "frosting", which not only weakens the anti-aging effect, but also causes a waste of antioxidant, resulting in certain economic losses and environmental pollution.

[0003] At present, the means to improve the migration problem of antioxidants between the macromolecular cross-linked networks of elastomers in the prior art is mainly to load small molecule antioxidants on a carrier, that is, to prepare a loaded antioxidant and then add it to rubber. Among them, antioxidant carriers mainly include carbon black, white carbon black, graphene and carbon nanotubes. However, carbon black has high energy consumption and serious environmental pollution. A large amount of CO2 is emitted during the production process, which aggravates the greenhouse effect; the production process of high-performance white carbon black is relatively complicated and expensive. At the same time, the vulcanization time of white carbon black filled rubber is relatively long and the vulcanization efficiency is low; the large-scale application of graphene and carbon nanotubes in the general field of rubber not only has high production costs, but also serious self-agglomeration phenomenon, and it is not easy to evenly load the antioxidant on its surface, thereby affecting the use effect of the loaded antioxidant.

[0004] Therefore, providing a supported antioxidant that can have a good anti-thermal oxidative aging effect on rubber has become a technical problem that urgently needs to be solved in the field. Summary of the invention

[0005] The purpose of the present invention is to provide a porous calcium silicate-supported antioxidant and a preparation method and application thereof. The porous calcium silicate-supported antioxidant provided by the present invention has excellent anti-thermal oxidation aging effect on rubber.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a porous calcium silicate supported antioxidant, comprising a porous calcium silicate carrier and an antioxidant supported on the surface of the porous calcium silicate carrier;

[0008] The mass of the antioxidant is 5-25% of the mass of the porous calcium silicate supported antioxidant.

[0009] Preferably, the antioxidant is one or more of quinoline antioxidant, p-phenylenediamine antioxidant, phenol thioester antioxidant, mercaptan antioxidant and phosphite antioxidant.

[0010] Preferably, the specific surface area of ​​the porous calcium silicate carrier is 30 to 100 m 2 / g, bulk density is 0.25~0.40g / cm 3 , the average particle size is 0.5~10μm.

[0011] The present invention also provides a method for preparing the porous calcium silicate supported antioxidant described in the above technical solution, comprising the following steps:

[0012] (1) mixing an antioxidant with a porous calcium silicate carrier, a surface modifier and a solvent to obtain a mixed slurry;

[0013] (2) The mixed slurry obtained in step (1) is mixed with water and then deposited to obtain a porous calcium silicate-supported antioxidant.

[0014] Preferably, the surface modifier in step (1) is a silane coupling agent, a polyacrylate or stearic acid.

[0015] Preferably, in step (1), the ratio of the mass of the surface modifier to the mass of the porous calcium silicate carrier is (0.9-3):50.

[0016] Preferably, the mixing process in step (2) is: pumping water into the mixed slurry; the pumping rate of the water is 1 to 10 mL / min.

[0017] Preferably, the mass of the water pumped in is 0.5 to 2 times the mass of the solvent in step (1).

[0018] Preferably, the deposition temperature in step (2) is 25-45°C.

[0019] The present invention also provides the use of the porous calcium silicate-supported antioxidant described in the above technical solution or the porous calcium silicate-supported antioxidant prepared by the preparation method described in the above solution in rubber.

[0020] The present invention provides a porous calcium silicate supported antioxidant, comprising a porous calcium silicate carrier and an antioxidant supported on the surface of the porous calcium silicate carrier; the weight of the antioxidant is 5-25% of the weight of the porous calcium silicate supported antioxidant. The present invention selects porous calcium silicate as the carrier of the antioxidant, which has a porous structure and a large specific surface area, and can play a good dispersing role on the antioxidant; and the porous calcium silicate carrier has a good adsorption effect, which is not only conducive to the antioxidant being firmly bonded to its surface and not easy to fall off, but also does not produce phase separation when added to rubber, and can effectively inhibit the migration of the antioxidant between the rubber cross-linked networks; in addition, the porous calcium silicate carrier has good dispersibility and a wide range of sources. The results of the embodiments show that the antioxidant in the porous calcium silicate-loaded antioxidant provided by the present invention is uniformly loaded on the surface of the porous calcium silicate carrier, and is used to prepare rubber products. The prepared rubber products have a high retention rate of tensile strength and elongation at break after aging at 100°C for 0 to 16 days, and can have good resistance to thermal oxidation aging at an aging temperature of 50 to 150°C within 4 days. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of the preparation principle of the porous calcium silicate supported antioxidant according to Example 2 of the present invention;

[0022] Figure 2 The infrared spectra of the porous calcium silicate supported antioxidant (ACS-4020) of Example 2 of the present invention, the antioxidant 4020 of Comparative Example 1 and the porous calcium silicate (ACS) of Comparative Example 2;

[0023] Figure 3 This is a scanning electron microscope (SEM) image of porous calcium silicate of comparative example 2 of the present invention;

[0024] Figure 4 This is a scanning electron microscope (SEM) image of the porous calcium silicate supported antioxidant of Example 2 of the present invention;

[0025] Figure 5 This is a transmission electron microscope (TEM) image of porous calcium silicate of comparative example 2 of the present invention;

[0026] Figure 6 The SEM, SEM-EDS, TEM, and TEM-EDS images of the porous calcium silicate-supported antioxidant of Example 2 of the present invention are shown in FIG. Figure 6 a is the SEM image, Figure 6 g is the TEM image, Figure 6 b~ Figure 6 f are the SEM-EDS images of Si, Ca, C, N, and O elements on the surface of porous calcium silicate-supported antioxidant, Figure 6 h~ Figure 6l are TEM-EDS images of Si, Ca, C, N and O elements on the surface of porous calcium silicate-supported antioxidant;

[0027] Figure 7 The rubber products of Application Example 1 of the present invention and Comparative Application Example 1 are bar graphs of tensile strength, elongation at break and hardness of the rubber products at 100° C. before aging, aging for 2 days, aging for 4 days, aging for 6 days, aging for 8 days, aging for 10 days, aging for 12 days, aging for 14 days and aging for 16 days, and their respective retention rate change curves;

[0028] Figure 8 The rubber products of Application Example 1 of the present invention and Comparative Application Example 1 are bar graphs of tensile strength, elongation at break and hardness aged for 4 days at different aging temperatures of 50°C, 75°C, 100°C, 125°C and 150°C, and their respective retention rate change curves;

[0029] Fig. 9 The thermogravimetric-infrared combined images of the rubber products of Application Example 1 of the present invention and Comparative Application Example 1; wherein, Fig. 9 a is the thermogravimetric-infrared combined graph of the rubber product of Application Example 1, Fig. 9 b is the thermogravimetric-infrared combined image of the rubber product of comparative application example 1. DETAILED DESCRIPTION

[0030] The purpose of the present invention is to provide a porous calcium silicate-supported antioxidant and a preparation method thereof. The porous calcium silicate-supported antioxidant provided by the present invention has an excellent anti-aging effect on rubber.

[0031] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0032] The present invention provides a porous calcium silicate supported antioxidant, comprising a porous calcium silicate carrier and an antioxidant supported on the surface of the porous calcium silicate carrier;

[0033] The mass of the antioxidant is 5-25% of the mass of the porous calcium silicate supported antioxidant.

[0034] The porous calcium silicate supported antioxidant provided by the present invention includes a porous calcium silicate carrier. The present invention selects porous calcium silicate as the carrier of the antioxidant, which has a porous structure and a large specific surface area, and can play a good dispersing effect on the antioxidant; and the porous calcium silicate carrier has a good adsorption effect, which is not only conducive to the antioxidant being firmly bonded to its surface and not easy to fall off, but also does not produce phase separation when added to rubber, and can effectively inhibit the migration of the antioxidant between the rubber cross-linked networks; in addition, the porous calcium silicate carrier has good dispersibility and a wide source.

[0035] In the present invention, the specific surface area of ​​the porous calcium silicate carrier is preferably 30 to 100 m2 / g, more preferably 40 to 90 m 2 / g, and the most preferred is 60 to 80 m 2 / g; the bulk density of the porous calcium silicate carrier is preferably 0.25 to 0.40 g / cm 3 , more preferably 0.26 to 0.38 g / cm 3 , and most preferably 0.28 to 0.32 g / cm 3 The average particle size of the porous calcium silicate carrier is preferably 0.5 to 10 μm, more preferably 1 to 8 μm, and most preferably 2 to 5 μm. The present invention is more conducive to uniformly and firmly loading the antioxidant by controlling the parameters of the porous calcium silicate carrier within the above range.

[0036] The present invention has no special requirements on the source of the porous calcium silicate, and any porous calcium silicate prepared by conventional methods in the art or commonly available on the market can be used.

[0037] The porous calcium silicate supported antioxidant provided by the present invention comprises an antioxidant supported on the surface of the porous calcium silicate carrier.

[0038] In the present invention, the antioxidant is preferably one or more of quinoline antioxidant, p-phenylenediamine antioxidant, phenol thioester antioxidant, mercaptan antioxidant or phosphite antioxidant. In the present invention, the quinoline antioxidant is preferably antioxidant AW; the p-phenylenediamine antioxidant is preferably antioxidant 4020; the phenol thioester antioxidant is preferably antioxidant 2246; the mercaptan antioxidant is preferably antioxidant ZMTI; the phosphite antioxidant is preferably antioxidant 168.

[0039] In the present invention, the weight of the antioxidant is 5-25% of the weight of the porous calcium silicate supported antioxidant, preferably 8-22%, and more preferably 10-20%. By controlling the loading amount of the antioxidant within the above range, the antioxidant is more conducive to being uniformly and firmly attached to the surface of the porous calcium silicate, and is not easy to separate when used to prepare rubber, which is more conducive to improving the heat aging resistance of rubber products.

[0040] The porous calcium silicate-supported antioxidant provided by the invention has good dispersibility and can effectively improve the heat aging resistance of rubber products.

[0041] The present invention also provides a method for preparing the porous calcium silicate supported antioxidant described in the above technical solution, comprising the following steps:

[0042] (1) mixing an antioxidant with a porous calcium silicate carrier, a surface modifier and a solvent to obtain a mixed slurry;

[0043] (2) The mixed slurry obtained in step (1) is mixed with water and then deposited to obtain a porous calcium silicate-supported antioxidant.

[0044] The invention mixes an antioxidant with a porous calcium silicate carrier, a surface modifier and a solvent to obtain a mixed slurry.

[0045] In the present invention, the surface modifier is preferably a silane coupling agent, polyacrylate or stearic acid. By adding a surface modifier and selecting the above types of surface modifiers, the present invention can improve the surface activity of porous calcium silicate, which is more conducive to the stable combination of the antioxidant and porous calcium silicate.

[0046] In the present invention, the ratio of the mass of the antioxidant to the mass of the porous calcium silicate carrier is preferably (20-40): (40-60), more preferably (25-35): (45-55), and most preferably 30: 50. The present invention controls the ratio of the mass of the antioxidant to the mass of the porous calcium silicate carrier within the above range, which is more conducive to uniformly and firmly loading the antioxidant on the surface of the porous calcium silicate carrier, while ensuring that the antioxidant has a high loading rate on the porous calcium silicate surface, so that the porous calcium silicate-loaded antioxidant with a target loading amount can be obtained.

[0047] In the present invention, the mass ratio of the surface modifier to the porous calcium silicate carrier is preferably (0.9-3):50, more preferably (1.5-2):50. The present invention is more conducive to improving the surface activity of porous calcium silicate by controlling the mass ratio of the surface modifier to the porous calcium silicate carrier within the above range, thereby efficiently adsorbing the antioxidant.

[0048] In the present invention, the solvent is preferably acetone or ethanol.

[0049] The present invention has no special limitation on the amount of the solvent, as long as the amount of the solvent can be used to evenly mix the antioxidant, the porous calcium silicate carrier and the surface modifier and fully immerse them.

[0050] In the present invention, the process of mixing the antioxidant with the porous calcium silicate carrier, the surface modifier and the solvent is preferably: the antioxidant is mixed with the solvent to obtain an antioxidant solution, then porous calcium silicate is added to the antioxidant solution to mix evenly, and finally the surface modifier is added for full impregnation. The present invention can ensure that the porous calcium silicate is fully impregnated after the raw materials are mixed by controlling the process of mixing the antioxidant with the porous calcium silicate carrier, the surface modifier and the solvent, thereby efficiently absorbing the antioxidant and achieving uniform and firm loading of the antioxidant.

[0051] In the present invention, the temperature for mixing the antioxidant with the porous calcium silicate carrier, the surface modifier and the solvent is preferably 25 to 45° C., more preferably 30 to 40° C. The present invention has no particular limitation on the mixing time, as long as the antioxidant, the porous calcium silicate carrier and the surface modifier are uniformly mixed and fully immersed.

[0052] After obtaining the mixed slurry, the present invention mixes the mixed slurry with water and then deposits it to obtain a porous calcium silicate supported antioxidant.

[0053] In the present invention, the process of mixing the mixed slurry with water is: pumping water into the mixed slurry. In the present invention, the pumping rate of the water is preferably 1 to 10 mL / min, more preferably 2 to 9 mL / min, and most preferably 3 to 8 mL / min. The present invention is more conducive to the uniform precipitation of the antioxidant from the organic phase and deposition on the surface of the porous calcium silicate by controlling the pumping rate of water within the above range, thereby ensuring uniform loading.

[0054] In the present invention, the mass of the water pumped in is preferably 0.5 to 2 times the mass of the solvent, and more preferably 1 to 1.5 times. By controlling the mass of the water pumped in within the above range, the antioxidant is more likely to be fully precipitated in the organic phase.

[0055] In the present invention, the deposition temperature is preferably 25-45° C., more preferably 30-40° C. The present invention controls the deposition temperature within the above range, which is more conducive to uniform loading of the antioxidant on the surface of porous sodium silicate.

[0056] After the deposition is completed, the present invention preferably sequentially performs solid-liquid separation, water washing and drying on the deposited product to obtain a porous calcium silicate-supported antioxidant.

[0057] The porous calcium silicate-loaded antioxidant prepared by the preparation method provided by the present invention can make the antioxidant uniformly and firmly loaded on the surface of the porous calcium silicate, which is more conducive to improving its thermal oxidation aging resistance for rubber products; and the preparation method is simple, the parameters are easy to control, the raw material sources are wide, the cost is low, and large-scale production is possible.

[0058] The present invention also provides the use of the porous calcium silicate-supported antioxidant described in the above technical solution or the porous calcium silicate-supported antioxidant prepared by the preparation method described in the above solution in rubber.

[0059] The porous calcium silicate-supported antioxidant provided by the present invention is used in rubber. The rubber product prepared has a high retention rate of tensile strength and elongation at break after aging at 100° C. for 0 to 16 days, and has good resistance to thermal oxidation aging at an aging temperature of 50 to 150° C. within 4 days.

[0060] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] Example 1

[0062] The porous calcium silicate supported antioxidant provided in this embodiment is composed of a porous calcium silicate carrier and an antioxidant supported on the surface of the porous calcium silicate carrier; the weight of the antioxidant is 23% of the weight of the porous calcium silicate supported antioxidant. The antioxidant is a quinoline antioxidant, and the bulk density of the porous calcium silicate carrier is 0.38 g / cm 3 , the average particle size is 1 μm, and the specific surface area is 100 m 2 / g.

[0063] The preparation method of the porous calcium silicate supported antioxidant is as follows:

[0064] (1) mixing an antioxidant with a porous calcium silicate carrier, a surface modifier (silane coupling agent) and a solvent (ethanol) to obtain a mixed slurry; specifically:

[0065] In a homogenizing reactor, at a temperature of 25°C, 30 g of quinoline antioxidant (anti-aging agent AW) was dissolved in 200 g of ethanol to prepare an antioxidant AW solution; 50 g of porous calcium silicate was weighed and added to the ethanol solution of antioxidant AW; after stirring evenly, 1.5 g of silane coupling agent (KH550) was added to the homogenizing reactor for full immersion to prepare a mixed slurry.

[0066] (2) mixing the mixed slurry obtained in step (1) with water and then depositing the mixture to obtain a porous calcium silicate supported antioxidant; specifically:

[0067] Using a peristaltic pump, 100 mL (100 g) of deionized water was pumped into the mixed slurry at a rate of 1 mL / min, and the antioxidant AW was precipitated at 25°C and deposited on the porous calcium silicate particles; finally, the deposited product was sequentially subjected to solid-liquid separation, water washing and drying to obtain a porous calcium silicate-loaded antioxidant.

[0068] Example 2

[0069] The porous calcium silicate supported antioxidant provided in this embodiment is composed of a porous calcium silicate carrier and an antioxidant supported on the surface of the porous calcium silicate carrier; the weight of the antioxidant is 19% of the weight of the porous calcium silicate supported antioxidant. The antioxidant is a p-phenylenediamine antioxidant, and the bulk density of the porous calcium silicate carrier is 0.32 g / cm 3 The average particle size is 2 μm and the specific surface area is 90 m 2 / g.

[0070] The preparation method of the porous calcium silicate supported antioxidant is as follows:

[0071] (1) mixing an antioxidant with a porous calcium silicate carrier, a surface modifier (silane coupling agent) and a solvent (acetone) to obtain a mixed slurry; specifically:

[0072] In a homogenizing reactor, at a temperature of 30° C., 30 g of p-phenylenediamine antioxidant (antioxidant 4020) was dissolved in 300 g of acetone to prepare an antioxidant 4020 solution; 50 g of porous calcium silicate was weighed and added to the acetone solution of antioxidant 4020; after stirring evenly, 2 g of silane coupling agent (3-mercaptopropyltriethoxysilane) was added and fully immersed in the homogenizing reactor to prepare a mixed slurry.

[0073] (2) mixing the mixed slurry obtained in step (1) with water and then depositing the mixture to obtain a porous calcium silicate supported antioxidant; specifically:

[0074] Using a peristaltic pump, 300 mL of deionized water was pumped into the mixed slurry at a rate of 3 mL / min, and the antioxidant 4020 was precipitated on the porous calcium silicate particles at 30°C; finally, the deposited product was sequentially subjected to solid-liquid separation, water washing and drying to obtain a porous calcium silicate-supported antioxidant (denoted as ACS-4020).

[0075] Example 3

[0076] The porous calcium silicate supported antioxidant provided in this embodiment is composed of a porous calcium silicate carrier and an antioxidant supported on the surface of the porous calcium silicate carrier; the weight of the antioxidant is 16% of the weight of the porous calcium silicate supported antioxidant. The antioxidant is a phenolic thioester antioxidant, and the bulk density of the porous calcium silicate carrier is 0.28 g / cm 3 The average particle size is 3 μm and the specific surface area is 80 m 2 / g.

[0077] The preparation method of the porous calcium silicate supported antioxidant is as follows:

[0078] (1) mixing an antioxidant with a porous calcium silicate carrier, a surface modifier (silane coupling agent) and a solvent (acetone) to obtain a mixed slurry; specifically:

[0079] In a homogenizing reactor, at a temperature of 35°C, 30 g of phenol thioester antioxidant (antioxidant 2246) was dissolved in 300 g of acetone to prepare an antioxidant 2246 solution; 50 g of porous calcium silicate was weighed and added to the acetone solution of antioxidant 2246; after stirring evenly, 0.9 g of silane coupling agent (Si69) was added and fully immersed in the homogenizing reactor to prepare a mixed slurry.

[0080] (2) mixing the mixed slurry obtained in step (1) with water and then depositing the mixture to obtain a porous calcium silicate supported antioxidant; specifically:

[0081] Using a peristaltic pump, 450 mL of deionized water was pumped into the mixed slurry at a rate of 5 mL / min, and the antioxidant 2246 was precipitated on the porous calcium silicate particles at 35°C; finally, the deposited product was sequentially subjected to solid-liquid separation, water washing and drying to obtain a porous calcium silicate-loaded antioxidant.

[0082] Example 4

[0083] The porous calcium silicate supported antioxidant provided in this embodiment is composed of a porous calcium silicate carrier and an antioxidant supported on the surface of the porous calcium silicate carrier; the weight of the antioxidant is 12% of the weight of the porous calcium silicate supported antioxidant. The antioxidant is a thiol antioxidant, and the bulk density of the porous calcium silicate carrier is 0.26 g / cm 3 The average particle size is 5 μm and the specific surface area is 60 m 2 / g.

[0084] The preparation method of the porous calcium silicate supported antioxidant is as follows:

[0085] (1) mixing an antioxidant with a porous calcium silicate carrier, a surface modifier (polyacrylic acid salt) and a solvent (acetone) to obtain a mixed slurry; specifically:

[0086] In a homogenizing reactor, at a temperature of 40°C, 30g of thiol antioxidant (anti-aging agent ZMTI) was dissolved in 300g of ethanol to prepare an antioxidant ZMTI solution; 50g of porous calcium silicate was weighed and added to the acetone solution of antioxidant ZMTI; after stirring evenly, 1.5g of polyacrylic acid salt (sodium polyacrylate) was added to the homogenizing reactor for full immersion to prepare a mixed slurry.

[0087] (2) mixing the mixed slurry obtained in step (1) with water and then depositing the mixture to obtain a porous calcium silicate supported antioxidant; specifically:

[0088] Using a peristaltic pump, 600 mL of deionized water was pumped into the mixed slurry at a rate of 7 mL / min, and the antioxidant ZMTI was precipitated on the porous calcium silicate particles at 40°C; finally, the deposited product was sequentially subjected to solid-liquid separation, water washing and drying to obtain a porous calcium silicate-loaded antioxidant.

[0089] Example 5

[0090] The porous calcium silicate supported antioxidant provided in this embodiment is composed of a porous calcium silicate carrier and an antioxidant supported on the surface of the porous calcium silicate carrier; the weight of the antioxidant is 10% of the weight of the porous calcium silicate supported antioxidant. The antioxidant is a phosphite antioxidant, and the bulk density of the porous calcium silicate carrier is 0.25 g / cm 3The average particle size is 8 μm and the specific surface area is 30 m 2 / g.

[0091] The preparation method of the porous calcium silicate supported antioxidant is as follows:

[0092] (1) mixing an antioxidant with a porous calcium silicate carrier, a surface modifier (stearic acid) and a solvent (ethanol) to obtain a mixed slurry; specifically:

[0093] In a homogenizing reactor, at a temperature of 45°C, 30 g of phosphite antioxidant (antioxidant 168) was dissolved in 500 g of ethanol to prepare an antioxidant 168 solution; 50 g of porous calcium silicate was weighed and added to the ethanol solution of antioxidant 168; after stirring evenly, 3 g of stearic acid was added to the homogenizing reactor for sufficient immersion to prepare a mixed slurry.

[0094] (2) mixing the mixed slurry obtained in step (1) with water and then depositing the mixture to obtain a porous calcium silicate supported antioxidant; specifically:

[0095] Using a peristaltic pump, 250 mL of deionized water was pumped into the mixed slurry at a rate of 9 mL / min, and the antioxidant 168 was precipitated on the porous calcium silicate particles at 45°C; finally, the deposited product was sequentially subjected to solid-liquid separation, water washing and drying to obtain a porous calcium silicate-loaded antioxidant.

[0096] Comparative Example 1

[0097] Phenylenediamine antioxidant (recorded as antioxidant 4020).

[0098] Comparative Example 2

[0099] The porous calcium silicate (denoted as ACS) in Example 2 was not subjected to loading treatment.

[0100] The schematic diagram of the loading principle of the porous calcium silicate supported antioxidant provided in Example 2 of the present invention is as follows: Figure 1 As shown. Figure 1 It can be seen that the surface of porous calcium silicate is rich in hydroxyl groups. It is fully immersed in the mixed slurry formed by mixing antioxidant 4020 with porous calcium silicate, surface modifier and acetone solvent. After deionized water is pumped in, antioxidant 4020 is precipitated from the acetone organic phase and then deposited on the surface of porous calcium silicate, thereby forming a porous calcium silicate-loaded antioxidant.

[0101] The porous calcium silicate supported antioxidant (ACS-4020) provided in Example 2, the antioxidant 4020 in Comparative Example 1, and the porous calcium silicate (ACS) in Comparative Example 2 were measured by infrared spectrometer. The infrared spectra obtained by the measurement are as follows: Figure 2 shown.

[0102] Depend on Figure 2 It can be seen that in the infrared spectrum of ACS-4020, characteristic peaks belonging to antioxidant 4020 appeared, located at 2955cm -1 , 1599cm -1 and 746cm -1 , which are respectively attributed to the stretching vibration peak of the CH bond of the alkyl group, the skeleton vibration peak of the benzene ring and the bending vibration of the five adjacent CH bonds in the monosubstituted benzene, which shows that the antioxidant 4020 has been successfully loaded on the porous calcium silicate.

[0103] The porous calcium silicate supported antioxidant provided in Example 2 was observed for microscopic morphology by scanning electron microscopy and transmission electron microscopy, and the element distribution was analyzed by energy dispersive spectrometer. The scanning electron microscopy and transmission electron microscopy images as well as SEM-EDS and TEM-EDS were observed as follows: Figures 3 to 6 As shown; among them, Figure 3 This is a scanning electron microscope (SEM) image of porous calcium silicate of comparative example 2 of the present invention; Figure 4 This is a scanning electron microscope (SEM) image of the porous calcium silicate supported antioxidant of Example 2 of the present invention; Figure 5 This is a transmission electron microscope (TEM) image of porous calcium silicate of comparative example 2 of the present invention; Figure 6 The SEM, SEM-EDS, TEM, and TEM-EDS images of the porous calcium silicate-supported antioxidant of Example 2 of the present invention are shown in FIG. Figure 6 a is the SEM image, Figure 6 g is the TEM image, Figure 6 b~ Figure 6 f are the SEM-EDS images of Si, Ca, C, N, and O elements on the surface of porous calcium silicate-supported antioxidant, Figure 6 h~ Figure 6 l are TEM-EDS images of Si, Ca, C, N and O elements on the surface of porous calcium silicate-supported antioxidant.

[0104] Will Figure 3 , Figure 4 and Figure 5 By comparison, it can be seen that the porous calcium silicate used as the carrier of the present invention is a layered structure of stacked sheets, has the structural conditions for loading the antioxidant, and can successfully load the antioxidant.

[0105] Depend on Figure 6 (af) It can be seen that the characteristic element N of antioxidant 4020 is uniformly loaded on the surface of porous calcium silicate, and Figure 6 (gl) It can be seen that the characteristic elements of antioxidant 4020 are evenly distributed on the surface of porous calcium silicate and between the sheets. This shows that the antioxidant 4020-loaded porous calcium silicate obtained by the preparation method described in Figure (1) has the antioxidant component evenly loaded.

[0106] Application Example 1

[0107] The porous calcium silicate-supported antioxidant provided in Example 2 of the present invention was used for rubber preparation. The specific preparation process was as follows: natural rubber, porous calcium silicate-supported antioxidant, zinc oxide, stearic acid, accelerator NS, and sulfur were added in order, mixed evenly on an open rubber mixer, and vulcanized and molded at 151°C to obtain a rubber product, which was recorded as ACS-4020 / NR.

[0108] Comparative application example 1

[0109] The diphenylenediamine antioxidant (antioxidant 4020) provided in comparative example 1 of the present invention and the unloaded porous calcium silicate provided in comparative example 2 are added to the rubber at the same time, and the same preparation method as in application example 1 is used to prepare the rubber. The obtained rubber product is recorded as ACS / 4020 / NR.

[0110] The rubber products of Application Example 1 and Comparative Application Example 1 were placed in hot air aging boxes respectively, and the rubber products were tested for their anti-thermal oxygen aging performance at different temperatures and for different times. The test results are as follows: Figure 7 and Figure 8 As shown in Table 1; Figure 7 The bar graphs of tensile strength, elongation at break and hardness of ACS-4020 / NR and ACS / 4020 / NR at 100°C for unaged, aged for 2 days, aged for 4 days, aged for 6 days, aged for 8 days, aged for 10 days, aged for 12 days, aged for 14 days and aged for 16 days and their respective retention curves; Figure 8 The bar graphs of tensile strength, elongation at break and hardness of ACS-4020 / NR and ACS / 4020 / NR aged for 4 days at different aging temperatures of 50℃, 75℃, 100℃, 125℃ and 150℃, as well as their respective retention curves are shown.

[0111] Depend on Figures 7-8 It can be seen that with the extension of aging time, the tensile strength and elongation at break of ACS-4020 / NR and ACS / 4020 / NR show an overall downward trend, and the hardness shows an upward trend. However, the retention rate of tensile strength and elongation at break of ACS-4020 / NR is better than that of ACS / 4020 / NR, and it can withstand thermal oxidation aging performance of 50-150°C within 4 days.

[0112] The ACS-4020 / NR provided in Application Example 1 of the present invention and the ACS / 4020 / NR provided in Comparative Application Example 1 were tested using a thermogravimetric infrared spectrometer. The obtained thermogravimetric infrared spectrometer is shown in the figure below. Fig. 9 As shown; among them, Fig. 9a is the thermogravimetric-infrared combined graph of the rubber product of Application Example 1, Fig. 9 b is the thermogravimetric-infrared combined image of the rubber product of comparative application example 1.

[0113] Depend on Fig. 9 It can be seen that during the entire thermal decomposition process, the volatile product structures of ACS / 4020 / NR and ACS-4020 / NR samples in the TG-IR determination process are basically the same, but the cracking time and content of some products show obvious differences. The weight loss temperatures of hydroxyl compounds, oxygen-containing, nitrogen-containing functional groups and aromatic compounds in the two samples are basically the same, but the weight loss of CO2 in the ACS-4020 / NR sample mainly exists after 300℃, while the weight loss of CO2 in the ACS / 4020 / NR sample shows a higher rate under the overall temperature conditions, indicating that the organic components in the ACS / 4020 / NR sample are relatively unstable. More importantly, the ACS / 4020 / NR sample shows a clear characteristic peak of long-chain alkanes in the infrared detection at 400-600℃, indicating that the C skeleton of natural rubber is cracked at a high speed, while the ACS-4020 / NR sample has no obvious changes. The overall results show that compared with the ACS / 4020 / NR sample, the ACS-4020 / NR sample has better thermal stability (anti-aging) performance.

[0114] In summary, the porous calcium silicate-supported antioxidant provided by the present invention can effectively improve the thermal-oxidative aging resistance of rubber products.

[0115] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A porous calcium silicate supported antioxidant, comprising a porous calcium silicate carrier and an antioxidant supported on the surface of the porous calcium silicate carrier; The mass of the antioxidant is 23-25% of the mass of the porous calcium silicate supported antioxidant; The specific surface area of ​​the porous calcium silicate carrier is 30 to 100 m 2 / g, bulk density is 0.25~0.40g / cm 3 , the average particle size is 0.5~10μm; The method for preparing the porous calcium silicate supported antioxidant comprises the following steps: (1) mixing an antioxidant with a porous calcium silicate carrier, a surface modifier and a solvent to obtain a mixed slurry; (2) The mixed slurry obtained in step (1) is mixed with water and then deposited to obtain a porous calcium silicate-supported antioxidant.

2. The porous calcium silicate supported antioxidant according to claim 1, characterized in that: The antioxidant is one or more of quinoline antioxidant, p-phenylenediamine antioxidant, phenol thioester antioxidant, mercaptan antioxidant and phosphite antioxidant.

3. The method for preparing the porous calcium silicate supported antioxidant according to any one of claims 1 to 2, comprising the following steps: (1) mixing an antioxidant with a porous calcium silicate carrier, a surface modifier and a solvent to obtain a mixed slurry; (2) The mixed slurry obtained in step (1) is mixed with water and then deposited to obtain a porous calcium silicate-supported antioxidant.

4. The preparation method according to claim 3, characterized in that: The surface modifier in step (1) is a silane coupling agent, polyacrylate or stearic acid.

5. The preparation method according to claim 3 or 4, characterized in that: In the step (1), the ratio of the mass of the surface modifier to the mass of the porous calcium silicate carrier is (0.9-3):

50.

6. The preparation method according to claim 3, characterized in that: The mixing process in step (2) is as follows: water is pumped into the mixed slurry; the pumping rate of the water is 1 to 10 mL / min.

7. The preparation method according to claim 6, characterized in that: The mass of the water pumped in is 0.5 to 2 times the mass of the solvent in step (1).

8. The preparation method according to claim 3, characterized in that: The deposition temperature in step (2) is 25-45°C.

9. Use of the porous calcium silicate-supported antioxidant as claimed in any one of claims 1 to 2 or the porous calcium silicate-supported antioxidant prepared by the preparation method as claimed in any one of claims 3 to 8 in rubber.

Citation Information

Patent Citations

  • Composite anti-aging agent, preparation method thereof and heat-resistant rubber material

    CN115536914A